The relative age effect in the two professional men's football leagues in spain - Yagüe, J. M.; Salguero, A.; Villegas, A.; Sánchez-Molina, J.; Molinero, O. (Journal of Sports Science & Medicine, 2023)
The age difference among individuals of the same group is known as Relative Age. Relative Age Effect refers to the consequences derived from it, such as delayed physical, cognitive and mental development of children born later in the year. The aim of this study was to observe the Relative Age Effect by analyzing players` dates of birth throughout three seasons in the two professional football competitions in Spain based on the game positions and the teams' classification at the end of the season. The sample was made up of players (n=4097) from both professional competitions (nLaLiga Santander=1864), and (nLaLiga Smartbank=2233). The data were collected from two public-access football statistics websites. The cut-off date was established on January 1, the year was divided into four quartiles (Q1: January-March, Q2: April-June, Q3: July-September and Q4: October-December). Results confirmed significant differences on dates of births` distribution (p<0.05) for the competitions — LaLiga Santander and LaLiga Smartbank — during three seasons, as well as for player position, with a larger effect observed for goalkeepers and defenders. Significant difference was also observed depending on classification. Results show a clear decreasing percentage of those born in quartile 4 in relation to those born in quartile 1, it can be concluded that the Relative Age Effect phenomenon is present in the Spanish professional football which may lead to an inappropriate talent selection technique in football, with recruitment oriented to the short term, to immediate results, and possibly caused by the early start of the player selection process.